Seismic magnitud calculation for Ñaña station - Jiménez, César (2010)
The seismic magnitude is a basic parameter which is related with the amount of energy released by an earthquake. The magnitude is a function of the signal energy and of the attenuation for the epicentral distance. The seismic station of Ñaña (NNA) belongs to the international network Incorporated Research Institutions for Seismology (IRIS), has a broadband sensor of three components. The acquisition of the signal is free via internet through AutoDRM protocol. In this work a mathematical algorithm is developed through the multiple linear regression method. The hipocentral data are obtained from the Instituto Geofisico del Peru (IGP) catalog, while the magnitudes are obtained from the National Earthquake Information Center (NEIC) catalog. The magnitude equation obtained obtained is accredit respect to the Mw magnitude of NEIC.